THE IMPACT OF TUTORING EXPERIENCE ON THE TEACHING CAREER IN MEDICAL EDUCATION (CIPEEX, 2025)
Academic peer tutoring (monitoria acadêmica) has been described as a bridge between students’ learning experience and their initiation into teaching in undergraduate medical education, fostering pedagogical competencies and collaborative learning environments. This study conducted a systematic literature review (PRISMA) to determine the extent to which peer tutoring influences the decision to pursue an academic career in medicine and to understand associated factors and perceived benefits among students interested in teaching. The Web of Science search (2020–2025) followed predefined inclusion/exclusion criteria and a two-stage screening (title/abstract and full text). Standardized data extraction covered authors, year, objective, method, main results, contributions, and limitations, with a predominantly qualitative synthesis.Thirty-six studies were identified; after PRISMA screening, 6 articles comprised the sample. Collectively, the literature indicates that peer tutoring strengthens didactic planning, communication, leadership, and the use of active learning methods, broadening understanding of the university teacher’s role and responsibilities and reinforcing interest in teaching. Peer-to-peer experiences report benefits not only for tutors but also for non-tutor students involved in activities, yielding collaborative learning gains and greater curricular engagement. International evidence shows a high intention to teach after residency (62% wish to teach students and 60% residents), while self-confidence remains moderate for didactic/procedural tasks such as clinical interview/physical examination (49%), lectures/didactics (42%), and procedural techniques (28%). Structured student-as-teacher programs are associated with curricular contributions and consolidation of interest in an academic career.Implications include institutionalizing structured tutoring pathways with faculty mentoring, formative feedback, and graduated teaching opportunities, alongside integrating active methodologies and assessments of pedagogical performance. Main limitations in the literature include methodological heterogeneity and a paucity of longitudinal evaluations measuring medium- and long-term teaching outcomes. In conclusion, academic peer tutoring is a relevant formative mechanism in medical education, with potential to guide institutional policies for student teacher-development and to encourage the choice of an academic career.
Keywords: Academic peer tutoring; Teacher training; Medical Education